Sleep duration and multimorbidity in Luxembourg: results from the European Health Examination Survey in Luxembourg, 2013–2015 - Valéry Bocquet; Saverio Stranges; Tatjana T Makovski (BMJ Open)
Objectives We estimated the prevalence of short sleep duration and multimorbidity in Luxembourg, and assessed whether sleep duration was associated with multimorbidity after adjusting for sociodemographic and behavioural characteristics.Design Cross-sectional study.Participants Data from 1508 Luxembourg residents (48% men and 52% women) aged 25 to 64 years came from the European Health Examination Survey 2013–2015.Outcome measures Short sleep duration and multimorbidity.Results Participants reported sleeping 6.95 hours/night during work days, nearly 1 hour less than during non-work days (7.86 hours/night). Nearly half of participants reported having been diagnosed with ≥2 chronic conditions/diseases. Short sleep duration was associated with the number of chronic conditions (OR 4.65, 95% CI 1.48 to 14.51; OR 7.30, 95% CI 2.35 to 22.58; OR 6.79, 95% CI 2.15 to 21.41 for 1, 2 and ≥3 chronic conditions/diseases, respectively), independently of socioeconomic and behavioural characteristics.Conclusions Health promotion programmes should aim at improving and promoting healthy lifestyles among the general population to improve sleep habits as well as decrease multimorbidity in middle-aged adults.